Factors Predicting Dating Violence Perpetration among Male and Female College Students - Baker, Colleen R.; Stith, Sandra M. (My University, 2010)
This study examined the importance of witnessing parental violence, experiencing childhood violence, problems with alcohol, length of relationship, relationship satisfaction, anger management skills, and partner’s use of physical and psychological aggression for male and female perpetrators of dating violence in college. For males, partner’s use of physical aggression, low levels of anger management skills, and high relationship satisfaction were the strongest predictors of physical aggression. For females, partner’s uses of physical and psychological aggression were the most important predictors of their use of physical aggression. The model in this study was a good predictor of male violence, accounting for 81% of the variance; however, it only accounted for 51% of the variance in female violence.
Keywords: Dating violence; Gender; Physical abuse; Psychological abuse; College students